2008
DOI: 10.1007/s10522-008-9134-x
|View full text |Cite
|
Sign up to set email alerts
|

Premature senescence of human endothelial cells induced by inhibition of glutaminase

Abstract: Cellular senescence is now recognized as an important mechanism of tumor suppression, and the accumulation of senescent cells may contribute to the aging of various human tissues. Alterations of the cellular energy metabolism are considered key events in tumorigenesis and are also known to play an important role for aging processes in lower eukaryotic model systems. In this study, we addressed senescence-associated changes in the energy metabolism of human endothelial cells, using the HUVEC model of in vitro s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
79
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 49 publications
10
79
0
Order By: Relevance
“…Microscopic evaluation of the SA-b-Gal activity showed that about 40% of the cells in the priorsenescent passage were active. The amount of positively stained cells increased to 50% at the senescent state, and confirmed the accumulation of SA-b-Gal active cells during senescence as found by others [15,17,31,32]. A strong induction of cell cycle protein p21 was observed in the cells at the prior-senescent state and the senescent state (Fig.…”
Section: Inhibition Of Cell Proliferationsupporting
confidence: 88%
See 1 more Smart Citation
“…Microscopic evaluation of the SA-b-Gal activity showed that about 40% of the cells in the priorsenescent passage were active. The amount of positively stained cells increased to 50% at the senescent state, and confirmed the accumulation of SA-b-Gal active cells during senescence as found by others [15,17,31,32]. A strong induction of cell cycle protein p21 was observed in the cells at the prior-senescent state and the senescent state (Fig.…”
Section: Inhibition Of Cell Proliferationsupporting
confidence: 88%
“…These studies revealed that senescence can be triggered or accelerated by various stresses like telomere shortening, DNA damage, oxidative stress, glycation, or overexpression of certain oncogenes [12,[15][16][17][18][19][20][21]. It is known that the effect of senescence on cell function and the surrounding tissues is strongly cell-type-dependent [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, premature senescence of human endothelial cells is induced by the inhibition of glutaminase (demonstrated by the use of a glutaminase inhibitor as 6-diaso-5-oxo-L-norleucine). 140 Senescence and apoptosis act as parallel pathways by which severely damaged cells are eliminated from the body by the innate immune system. 141 Programmed cell death pathways are promising targets for interventions in aging and aging-related diseases.…”
Section: Impact Of Aging On Glutamine Metabolism At the Cellular Levelmentioning
confidence: 99%
“…However, when oxidative stress impairs metabolic enzymes and glycolysis, glutamine-derived ATP production rapidly increases (Hinshaw and Burger, 1990). Blocking the conversion of glutamine into glutamate by GLS knockdown inhibits proliferation and induces a senescence-like state in endothelial cells (Unterluggauer et al, 2008). GATs also produce NH 3 from glutamine but, instead of being released, the NH 3 is transferred onto another molecule.…”
Section: Amino Acid Metabolismmentioning
confidence: 99%